2020
DOI: 10.1186/s11658-020-00229-6
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin suppresses epithelial–mesenchymal transition in human non-small cell lung cancer cells by restraining RHBDD1

Abstract: Background: Rhomboid domain containing 1 (RHBDD1) plays a crucial role in tumorigenesis. Silibinin, which is a natural extract from milk thistle, has shown antitumor effects against various tumors. Here, we investigate whether silibinin affects the function of RHBDD1 in non-small cell lung cancer (NSCLC) cell proliferation, migration and invasion. Methods: The Oncomine database and an immunohistochemistry (IHC) assay were used to determine the RHBDD1 expression levels in lung cancer tissues. The associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…EMT is critical process during tumor progression and metastasis in which epithelial cells gain mesenchymal features to have better abilities for invasion. This process is characterized by E-cadherin downregulation and vimentin upregulation [108][109][110]. The WNT signaling pathway regulates cell proliferation, polarity and death during embryogenesis [111].…”
Section: Wnt and Hedgehog Signaling Pathwaysmentioning
confidence: 99%
“…EMT is critical process during tumor progression and metastasis in which epithelial cells gain mesenchymal features to have better abilities for invasion. This process is characterized by E-cadherin downregulation and vimentin upregulation [108][109][110]. The WNT signaling pathway regulates cell proliferation, polarity and death during embryogenesis [111].…”
Section: Wnt and Hedgehog Signaling Pathwaysmentioning
confidence: 99%
“…A drug could be considered for anticancer studies if it can act on some of the hallmarks of cancer, including proliferative signaling, resistance to cell death, evasion of growth suppressors, induction of replicative immortality, initiation of angiogenesis, and stimulation of invasion and metastasis [ 19 ]. The anticancer ability of silibinin against lung cancer is well known [ 36 , 37 ] and our results also showed that increasing concentrations of silibinin induced cell death in NSCLC cells (A549, H292, and H460) [ 28 ].…”
Section: Discussionmentioning
confidence: 65%
“…Silencing of RHBDD1 can inhibit cell proliferation and growth in glioblastoma, colorectal, breast cancer, and hepatocellular carcinoma. Silybin inhibits the epithelial‐mesenchymal transformation of NSCLC cells by inhibiting RHBDD1 and exerts anti‐tumor effects on NSCLC cells 241 . Reverse inducible cysteine‐rich protein with Kazal motif (RECK) is a membrane‐anchored glycoprotein that negatively regulates matrix metalloproteinase (MMP) and plays an integral role in cancer invasion and metastasis.…”
Section: Anti‐tumor Mechanismmentioning
confidence: 99%